Pengaruh Fixed Asset Intensity, Karakter Eksekutif, dan Leverage terhadap Penghindaran Pajak - Pratiwi Cynthia Lukito; Rachmawati Meita Oktaviani (Politeknik Ganesha Medan, 2022)
This study aims to examine whether the intensity of fixed asset, executive character, and leverage have an effect on tax avoidance. Tax avoidance is an activity to avoid paying taxes legally in accordance with the provisions of the legislation carried out by the company in order to be able to pay the minimum tax possible to the state treasury. Population in this study were manufacture companies listed in Indonesia Stock Exchange (IDX) during the period 2017 to 2020. The sampling technique used purposive sampling and obtained 54 companies, so that the total sample obtained for 4 years was 216 research samples. This study used quantitative method and the analysis by data panel regression. Tax avoidance proxy by cash effective tax rate (CETR) which is cash paid in cash for pay taxes. Partially shows that the intensity of fixed assets has no effect on tax avoidance, executive character has a significant positive effect on tax avoidance, and leverage has no effect on tax avoidance. While the results of this study indicate that the intensity of fixed assets, executive character, and leverage simultaneously have a significant effect on tax avoidance with the value of Prob (F-statistic) 0.000000. Result of Adjusted R-square shows of fixed Asset intensity, executive character, and leverage have a significant effect on tax avoidance is 0.3343 or 33.43%.